EU Strategic Autonomy and the Perceived Challenge of China: Can Critical Hubs Be De-weaponized? - Poutala Tero; Sinkkonen Elina; Mattlin Mikael (Kluwer Law International, 2022)
Geoeconomic competition, supply security vulnerabilities and complex technological dependencies challenge the European Union’s ‘strategic autonomy’. Evolving from more traditional security/ defence notions, a broader definition of strategic autonomy encompasses also economic dimensions. Economic resilience underpins security and defence arrangements. The EU has lacked instruments for protection against ‘predatory’ strategic investments by external actors, and technological dependence on potential strategic rivals. This article analyses two critical hubs, or potential ‘chokepoints’, in the EU’s attempts to achieve strategic autonomy – critical maritime transport infrastructure and 5G – as well as countermeasures developed by the EU. Chinese enterprises have made strategic investments in key EU infrastructure and high-tech industries over the past decade. In response, the EU has established an investment screening framework to screen (authorize, issue condition, prohibit or unwind) inward foreign direct investment (FDI) on security or public order grounds, and activated a mechanism for the enhancement of coordination and cooperation between the Commission and Member States. The EU has also sought to reduce reliance on Chinese suppliers by introducing the ‘5G toolbox’. We argue that the EU aims to ‘de-weaponize’ these two potential chokepoints. However, our article concludes that the political goal of strategic autonomy vis-à-vis external actors is hampered by the competence limitations of the Union to act in critical areas. Ultimately, much of the heavy lifting on implementing EU policy goals still falls upon Members States with varied economic and security interests.